Fluid-structure interaction computational analysis and experiments of tsunami bore forces on coastal bridges - Mazinani, I. (Emerald Group Holdings Ltd., 2021)
Purpose: Two disastrous Tsunamis, one on the west coast of Sumatra Island, Indonesia, in 2004 and another in North East Japan in 2011, had seriously destroyed a large number of bridges. Thus, experimental tests in a wave flume and a fluid structure interaction (FSI) analysis were constructed to gain insight into tsunami bore force on coastal bridges. Design/methodology/approach: Various wave heights and shallow water were used in the experiments and computational process. A 1:40 scaled concrete bridge model was placed in mild beach profile similar to a 24 Ã 1.5 Ã 2 m wave flume for the experimental investigation. An Arbitrary Lagrange Euler formulation for the propagation of tsunami solitary and bore waves by an FSI package of LS-DYNA on high-performance computing system was used to evaluate the experimental results. Findings: The excellent agreement between experiments and computational simulation is shown in results. The results showed that the fully coupled FSI models could capture the tsunami wave force accurately for all ranges of wave heights and shallow depths. The effects of the overturning moment, horizontal, uplift and impact forces on a pier and deck of the bridge were evaluated in this research. Originality/value: Photos and videos captured during the Indian Ocean tsunami in 2004 and the 2011 Japan tsunami showed solitary tsunami waves breaking offshore, along with an extremely turbulent tsunami-induced bore propagating toward shore with significantly higher velocity. Consequently, the outcomes of this current experimental and numerical study are highly relevant to the evaluation of tsunami bore forces on the coastal, over sea or river bridges. These experiments assessed tsunami wave forces on deck pier showing the complete response of the coastal bridge over water. Â© 2021, Emerald Publishing Limited.